Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Soo given x + y = 4

and 2x - 5y = 1

so from x + y = 4 ⇒ x = 4 - y

so 2x - 5y = 1 ⇒ 2(4 - y ) - 5y = 1

⇒ 8 - 7y = 1

⇒y = 1

so x = 4 - 1 = 3

so x = 3 , y = 1

and 2x - 5y = 1

so from x + y = 4 ⇒ x = 4 - y

so 2x - 5y = 1 ⇒ 2(4 - y ) - 5y = 1

⇒ 8 - 7y = 1

⇒y = 1

so x = 4 - 1 = 3

so x = 3 , y = 1

2x-5y=1------------eq(2)

(1)*5 = 5x+5y=20

(2)*1

__=2x-5y=1__

7x=21

=x=3

putting x value in (1)

2x-5y=1

=6-5y=1

=-5y=-5

=y=1